The Authors Are Interested in Conducting Research on Human Resource Management Audits on HR Recruitment to Assess Effectiveness in Jampang Kulon Hospital - Mutiara Priscilla; Sulaeman Sulaeman; Venita Sofiani (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
This study aims to determine: 1. To determine HR recruitment at Jampang Kulon Hospital 2. To determine HR management audit at Jampang Kulon Hospital 3. To determine the effectiveness of HR recruitment at Jampang Kulon Hospital. These variables consist of management audit and HR recruitment as independent variables, effectiveness as dependent variable. The method used in this research is a qualitative method, the type of data used in this study is secondary data, namely data that is generated from the interview process and direct observation to the informant. Secondary data is obtained through the process of observation and interviews as well as data evidence in the form of documentation and data from the archives of the company where the research is carried out with the consideration of previous research. In this study, it was found that the management audit process for recruitment carried out at Jampangkulon Hospital could increase the company's effectiveness on the recruitment process carried out at Jampangkulon Hospital.